Late Antique Responses to the Arab Conquest - Weststeijn, Johan; Eijnde, Floris van den; Bent, Josephine van den (Cultural Interactions in the Mediterranean, 2022)
Late Antique Responses to the Arab Conquests is a showcase of new discoveries in an exciting and rapidly developing field: the study of the transition from Late Antiquity to Early Islam. The contributors to this volume engage with previously neglected sources, such as Arabic rock inscriptions, papyri and Byzantine archaeological remains. They also apply new interpretative methods to the literary tradition, reading the Qur'an as a late antique text, using Arabic poetry as a source to study the gestation of an Arab identity, and extracting settlement patterns of the Arabian colonizers in order to explain regional processes of Arabicization and Islamization. This volume shows how the Arab conquests changed both the Arabian conquerors and the conquered.